1994
DOI: 10.1017/s0950268800057423
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of verocytotoxin–producing, enteroaggregative and diffusely adherentEscherichia coliin different diarrhoeal states

Abstract: SUMMARYOne hundred and eighty-one stool specimens from patients with various types of diarrhoea (135 patients) or from non-diarrhoeal controls (23 acute medical patients, 23 inflammatory bowel disease in remission) were investigated using a colony-blot DNA hybridization assay for the presence of Verocytotoxin-producing (VTEC), enteroaggregative (EAggEC) and diffusely adherent (DAEC) Escherichia coli. Twelve patients had probe-positive EAggEC in the stool and 8 of these had diarrhoea, 6 following recent travel.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…It was recently shown that some E. coli strains are abnormally predominant in early and chronic ileal lesions observed in CD (10,11,22,45) and that E. coli from IBD patients shows more ability to adhere to epithelia (14,68). However, data from studies on adherence are inconsistent (13,34). Finally, a new E. coli strain, named LF82, isolated from the ileal mucosa of a patient with CD showed strong invasive ability in vitro (10,11) and was able to survive and replicate within macrophages (29).…”
Section: Vol 71 2003mentioning
confidence: 99%
“…It was recently shown that some E. coli strains are abnormally predominant in early and chronic ileal lesions observed in CD (10,11,22,45) and that E. coli from IBD patients shows more ability to adhere to epithelia (14,68). However, data from studies on adherence are inconsistent (13,34). Finally, a new E. coli strain, named LF82, isolated from the ileal mucosa of a patient with CD showed strong invasive ability in vitro (10,11) and was able to survive and replicate within macrophages (29).…”
Section: Vol 71 2003mentioning
confidence: 99%
“…Moreover, examination of a large number of human diarrhea-associated DAEC strains has shown that only two carried the daaE gene, suggesting that the F1845 fimbria is rare among diarrheagenic DAEC strains (59). In addition, epidemiological studies in various areas of the world are inconclusive with regard to a role of daaC-positive E. coli strains in diarrhea in children or adults (13,48,50,99,(107)(108)(109)(110)(111)(112)(113)(114)(115). However, the relationship between Afa/Dr DAEC and diarrhea in children as a function of age has been more convincingly demonstrated in age cross-sectional studies showing an increased incidence in children Ͻ1 to 5 years of age.…”
Section: Diarrheamentioning
confidence: 99%
“…Most of the epidemiological studies conducted in various areas of the world that were intended to identify Afa/Dr DAEC as cause of diarrhea in children over 5 years of age and in adults were inconclusive, as the same numbers of daaC-positive strains were found in cases and controls (13,48,50,71,99,(107)(108)(109)(110)(111)(112)(113)(114)(115)141). This observation highlights the existence of asymptomatic carriers of intestinal Afa/Dr DAEC strains and suggests that these pathogenic E. coli strains can be tolerated or controlled if the mature intestinal epithelial barrier is in a healthy condition.…”
Section: Intestinal Asymptomatic Portagementioning
confidence: 99%
“…Strains were isolated from both outbreaks and sporadic cases of diarrhoeal disease; one outbreak occurred in a hospital and involved elderly patients. EAggEC has also been described as a potential cause of travellers' diarrhoea in patients returning to the UK from a variety of locations (Brook et al 1994;Scotland et al 1994). However, Cohen et al (1993) showed that although EAggEC colonization rates of travellers in the US were high, there was no association between these organisms and diarrhoea in adults.…”
Section: ------------------------------------------------------------mentioning
confidence: 99%